1993
DOI: 10.1007/bf02382660
|View full text |Cite
|
Sign up to set email alerts
|

The association between rank, mating effort, and reproductive success in male Barbary macaques (Macaca sylvanus)

Abstract: ABSTRACT. The association between social rank, mating effort, and reproductive success of male Barbary macaques (Macaca sylvanus) has been evaluated by longterm behavioral observations and subsequent paternity determination via oligonucleotide DNA fingerprinting in a large semifreeranging group. All offspring born between 1985 and 1988 that survived to at least 1 year of age (n = 75) were available for paternity testing. The exclusion of all but one of the potential fathers from paternity was possible in 70 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 37 publications
3
34
3
Order By: Relevance
“…For example, Bauers and Hearn (1994) used DNA fingerprinting to assign paternity to offspring born in a captive colony of stumptailed macaques (Macaca arctoides) at the Wisconsin Regional Primate Center and found that the alpha male was responsible for siring all but one of 27 offspring born in an 8.5-year period. Similarly, Paul et al (1993) found a clear, positive association between male rank and reproductive success during 3 of 4 mating seasons in a semifreeranging group of Barbary macaques (Macaca sylvanus). Dixson et al (1993) also found that male dominance rank strongly determined reproductive success in a semifree-ranging colony of mandrills (Mandrillus sphinx): over a 5-year period, only the two most dominant adult males in the colony sired infants.…”
Section: Studies Of Mating Systems and Reproductive Strategiesmentioning
confidence: 83%
“…For example, Bauers and Hearn (1994) used DNA fingerprinting to assign paternity to offspring born in a captive colony of stumptailed macaques (Macaca arctoides) at the Wisconsin Regional Primate Center and found that the alpha male was responsible for siring all but one of 27 offspring born in an 8.5-year period. Similarly, Paul et al (1993) found a clear, positive association between male rank and reproductive success during 3 of 4 mating seasons in a semifreeranging group of Barbary macaques (Macaca sylvanus). Dixson et al (1993) also found that male dominance rank strongly determined reproductive success in a semifree-ranging colony of mandrills (Mandrillus sphinx): over a 5-year period, only the two most dominant adult males in the colony sired infants.…”
Section: Studies Of Mating Systems and Reproductive Strategiesmentioning
confidence: 83%
“…This can occur, for example, if coalitions serve to undercut the intrinsic power of high-ranking males or intimidate them, thus leading high-rankers to show some restraint in mating competition, but without changing ranks. Although it is difficult to demonstrate the function of coalitions when no immediate effects are visible, there is evidence for hierarchy-levelling coalitions in Barbary macaques (Kuester & Paul, 1992;Paul et al, 1993;Bissonnette, 2009;Bissonnette et al, 2009a). In this species, older adult males often launch coalitionary attacks during the mating season but when no female is directly at stake, apparently as a means of driving away more dominant, younger competitors (Berghänel et al, 2010;Bissonnette et al, 2011).…”
Section: Increasing Access To Matesmentioning
confidence: 99%
“…Paul et al (1993) found correlations between male rank and male reproductive success in 3 of 4 mating seasons, but only when subadult males were included in the analysis. In a different study, von Segesser et al (1995) demonstrated that out of 10 adult and subadult males at least 5 and possibly as many as 8 fathered infants.…”
Section: Introductionmentioning
confidence: 99%